Phytoremediation of pharmaceuticals--preliminary study - Kotyza, Jan; Soudek, Petr; Kafka, Zdenĕk; Vanĕk, Toás (International journal of phytoremediation, 2010)
Phytoremediation of selected pharmaceuticals (diclofenac, ibuprofen, and acetaminophen) using Armoracia rusticana and Linum usitatissimum cell cultures and by hydroponically cultivated Lupinus albus, Hordeum vulgaris, and Phragmites australis plants in laboratory conditions is described. During in vitro experiments, the best results for acetaminophen were achieved using Armoracia rusticana hairy root cultures, where 100% of the starting amount was removed from the media during eight days. Total removal of ibuprofen and diclofenac was achieved using a Linum usitatissimum suspension culture after one and six days, respectively. In the hydroponic arrangement, the best results were achieved for Lupinus, where acetaminophen was totally removed from media during two or four days in concentrations of 0.1 or 0.2 mM, respectively. The best effectiveness of ibuprofen removal (50% of starting amount) was found in case of Phragmites. Effectiveness of all tested plants for diclofenac removal was low. The best removal was achieved using Phragmites in the case of 0.2 mM concentration-67% of the starting amount and Hordeum for 0.1 mM starting concentration, 56%.
Keywords: Biodegradation, Environmental; biodegradace; rostliny; Diclofenac; paracetamol; Pharmaceutical Preparations; Acetaminophen; ibuprofen; diklofenak; léčivé přípravky; testy toxicity; Ibuprofen; hydroponie; Hydroponics; Toxicity Tests; Plants